Interactive effects of temperature, food and skeletal mineralogy mediate biological responses to ocean acidification in a widely distributed bryozoan. Issue 1853 (19th April 2017) - Swezey, Daniel S.; Bean, Jessica R.; Ninokawa, Aaron T.; Hill, Tessa M.; Gaylord, Brian; Sanford, Eric
Abstract : Marine invertebrates with skeletons made of high-magnesium calcite may be especially susceptible to ocean acidification (OA) due to the elevated solubility of this form of calcium carbonate. However, skeletal composition can vary plastically within some species, and it is largely unknown how concurrent changes in multiple oceanographic parameters will interact to affect skeletal mineralogy, growth and vulnerability to future OA. We explored these interactive effects by culturing genetic clones of the bryozoan Jellyella tuberculata (formerly Membranipora tuberculata ) under factorial combinations of dissolved carbon dioxide (CO2 ), temperature and food concentrations. High CO2 and cold temperature induced degeneration of zooids in colonies. However, colonies still maintained high growth efficiencies under these adverse conditions, indicating a compensatory trade-off whereby colonies degenerate more zooids under stress, redirecting energy to the growth and maintenance of new zooids. Low-food concentration and elevated temperatures also had interactive effects on skeletal mineralogy, resulting in skeletal calcite with higher concentrations of magnesium, which readily dissolved under high CO2 . For taxa that weakly regulate skeletal magnesium concentration, skeletal dissolution may be a more widespread phenomenon than is currently documented and is a growing concern as oceans continue to warm and acidify.